The Impact of Severe Acute Respiratory Syndrome on Otorhinolaryngological Services at The Prince of Wales Hospital in Hong Kong - Vlantis, Alexander C. (Laryngoscope, 2009)
Objectives/Hypothesis The objective was to describe the impact of severe acute respiratory syndrome (SARS) on the services of the division of otorhinolaryngology—head and neck surgery at an academic tertiary referral hospital in Hong Kong. Study Design Descriptive. Methods Records of general and subspecialty outpatient attendance, ward admissions, ward bed occupancy, and elective and emergency surgery were obtained for the period since the SARS outbreak and for an equivalent period before the outbreak. The changes in these parameters were determined against the background of new SARS cases. Results Since the outbreak of SARS in March 2003, the weekly outpatient clinic attendance has declined by 59%, the number of operations performed by 79%, the average ward bed occupancy rate by 79% and the daily admission rate by 84%. A dramatic increase of 300% in the number of patients defaulting on their outpatient appointments was recorded. Conclusion The substantial decrease in otorhinolaryngological services at an academic tertiary referral hospital in Hong Kong has been multifaceted. The decrease in attendance at the outpatient clinics reflects the increased number of patients defaulting on their appointments. Nonessential elective surgery was suspended soon after the outbreak, accounting for the decrease in the number of surgical procedures performed and partially for the decrease in ward bed occupancy and ward admissions. The temporary closure of the accident and emergency department contributed to the decrease in ward admissions and emergency surgical procedures. The reduced service offered by the hospital is having an impact on the quality of care available to patients with non–life‐threatening otorhinolaryngological conditions.